Rethinking Social Support and Conflict: Lessons from a Study of Women Who Have Separated from Abusive Partners - Sepali Guruge; Marilyn Ford-Gilboe; Joan Samuels-Dennis; Colleen Varcoe; Piotr Wilk; Judith Wuest (Hindawi Limited, 2012)
Relationships have both positive and negative dimensions, yet most research in the area of intimate partner violence (IPV) has focused on social support, and not on social conflict. Based on the data from 309 English-speaking Canadian women who experienced IPV in the past 3 years and were no longer living with the abuser, we tested four hypotheses examining the relationships among severity of past IPV and women's social support, social conflict, and health. We found that the severity of past IPV exerted direct negative effects on women's health. Similarly, both social support and social conflict directly influenced women's health. Social conflict, but not social support, mediated the relationships between IPV severity and health. Finally, social conflict moderated the relationships between social support and women's health, such that the positive effects of social support were attenuated in the presence of high levels of social conflict. These findings highlight that routine assessments of social support and social conflict and the use of strategies to help women enhance support and reduce conflict in their relationships are essential aspects of nursing care.